PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERORIENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI SISTEM PENCERNAAN KELAS VIII SMP - Lisa Susanti; Evi Suryawati; Arnentis ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of  this research was to increase critical thinking skill on the subject digestion system grade VIII junior high school. This research was conducted at the Laboratory of Biology Department of the University of Riau PMIPA FKIP and SMPN 23 Pekanbaru in March to September 2016. The research is a research development by using ADDIE model of integration to the stage of development. There are 5 LKS developed. Instruments of data collection in this study is the validation sheet LKS, and questionnaire responses of learners. After LKS developed, validated by 4 validator then the tests I in the 4th semester 20 students of biology education FKIP UR, and a second trial on 20 students of Class VIII SMPN 23 Pekanbaru. The tests showed the average score feasibility aspects of the content of 5 LKS developed very valid category is 4.21, the average score 4.34 categories designing aspect is very valid, and the mean score of the pedagogic aspect is 4.69 very valid category. The mean overall score of the fifth aspect is 4.41 LKS very valid category. I trial results showed the average score 4.21 with very good category. II trial results showed a mean score of 4.57 in very good categories. The results of the analysis of the answers to the second trial showed a mean value of 87 in good categories. LKS oriented discovery learning model can increase the understanding and knowledge about the digestion system and can increase critical thinking skill of student.